Connubial ecthyma gangrenosum in a healthy couple - Pavlović, Miloš (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2015)
Ecthyma gangrenosum is a relatively rare cutaneous infection generally thought to be Iinked to sepsis or bacteremia caused by Pseudomonas aeruginosa in severely iII or otherwise immunocompromised patients. Here we report on a healthy middle-aged couple with a typical ecthyma gangrenosum lesion on their thighs, obviously caused by spreading through intimate contact be- tween two skin surfaces: a sort of "consort kissing ulcer." Although they declined to allow microbiological sampling, the lesions gradually but completely regressed with oral ciprofloxacin treatment, leaving atrophic scars.
Keywords: bakterijske infekcije; dermatologija; ecthyma gangrenosum; infekcije; lesions; lezije; skin infection